Study of the peak oxygen uptake and maximal heart rate in wrestlers - Cuadra, D. (International Journal of Wrestling Science, 2019)
Compare values of oxygen uptake in treadmill against SWFT by ergoespirometry (ERGO) analysis in wrestling athletes.Relative oxygen consumption (VO2/Kg) peak Respiratory quotient (RER) Oxygen pulse (VO2/HR) Maximal heart rate (HRmax) Design Descriptive study of female and male cadets (n=10) of freestyle wrestling in pre-season at the Olympic Training Centre.